High sensitivity of melatonin suppression response to evening light in preschool‐aged children. Issue 2 (8th January 2022) - Hartstein, Lauren E.; Behn, Cecilia Diniz; Akacem, Lameese D.; Stack, Nora; Wright, Kenneth P.; LeBourgeois, Monique K.
Abstract: Light at night in adults suppresses melatonin in a nonlinear intensity‐dependent manner. In children, bright light of a single intensity before bedtime has a robust melatonin suppressing effect. To our knowledge, whether evening light of different intensities is related to melatonin suppression in young children is unknown. Healthy, good‐sleeping children (n = 36; 3.0–4.9 years; 39% male) maintained a stable sleep schedule for 7 days followed by a 29.5‐h in‐home dim‐light circadian assessment (~1.5 lux). On the final night of the protocol, children received a 1‐h light exposure (randomized to one of 15 light levels, ranging 5–5000 lux, with ≥2 participants assigned to each light level) in the hour before habitual bedtime. Salivary melatonin was measured to calculate the magnitude of melatonin suppression during light exposure compared with baseline levels from the previous evening, as well as the degree of melatonin recovery 50 min after the end of light exposure. Melatonin levels were suppressed between 69.4% and 98.7% ( M  = 85.4 ± 7.2%) during light exposure across the full range of intensities examined. Overall, we did not observe a light intensity‐dependent melatonin suppression response; however, children exposed to the lowest quartile of light intensities (5–40 lux) had an average melatonin suppression (77.5 ± 7.0%) which was significantly lower than that observed at each of the three higher quartiles of light intensities (86.4 ± 5.6%, 89.2 ± 6.3%, and 87.1 ± 5.0%, respectively). We further found that melatonin levels remained below 50% baseline for at least 50 min after the end of light exposure for the majority (62%) of participants, and recovery was not influenced by light intensity. These findings indicate that preschool‐aged children are highly sensitive to light exposure in the hour before bedtime and suggest the lighting environment may play a crucial role in the development and the maintenance of behavioral sleep problems through impacts on the circadian timing system.